DC allowable electric field strength for naphthenic‐based and paraffin‐based transformer oils - Chunjia Gao; Bo Qi; Binhao Chen; Juzhen Wu; Chengrong Li (High Voltage)
Abstract Currently, the design of transformers insulation predominantly depends on the allowable alternating current (AC) field values for insulating oil established by Weidmann in the 1980s, lacking the research under direct current (DC) voltage for converter transformers. This study selects naphthenic oils and paraffin‐based oil transformer oil as research subjects, establishing a practical measurement platform to ascertain the oil breakdown characteristics under DC voltage. Furthermore, it statistically analyses the allowable DC field values of the oil. The findings elucidate that (1) the three‐parameter Weibull distribution is more suitable to conduct a statistical analysis for oil breakdown probability, yielding a fitting degree up to 99.95%. (2) For a constant electrode spacing, a 14.81% voltage increment escalates the breakdown probability of the oil gap from 3.33% to 73.33%. Concurrently, an increase in electrode spacing leads to a substantial decrement in the breakdown field strength of transformer oil, with KI25X experiencing a 54.51% reduction as electrode spacing extends from 5 to 25 mm. (3) The constant terms of the allowable DC field strength for S4, KI50X, and KI25X are found to be 19.728, 17.221, and 19.281, respectively. (4) A thorough analysis for differences in physicochemical properties and electrical parameters elucidates the variations in insulation properties across different transformer oils. The findings presented in this study offer essential theoretical and technical foundations for the design, evaluation, and enhancement of insulation structures in converter transformers.